2012
DOI: 10.1016/j.ijhydene.2011.10.123
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic decomposition of biogas to produce H2-rich fuel gas and carbon nanofibers. Parametric study and characterization

Abstract: One of the main problems that our society must deal with in a near future is the progressive substitution of traditional fossil fuels by different energy sources, such as renewable energies. In this context, biogas will play a vital role in the future. Nowadays, one of the most important uses of biogas is the production of heat and electricity from its direct combustion in co-generation plants. An interesting alternative consists on its direct valorisation to produce a syn-gas that can be further processed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Nevertheless, the exploitation of biogas for different applications appears as an interesting option, particularly when considering its renewable origin. In this context, the Catalytic Decomposition of Biogas (CDB) to simultaneously produce syngas (SG) with high hydrogen contents and bio-carbon nanofibers (BCNFs) has been studied in detail [18,19]. As CNFs, BCNFs from biogas have initially a certain degree of structural order and therefore, they are classified within graphitic carbons.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the exploitation of biogas for different applications appears as an interesting option, particularly when considering its renewable origin. In this context, the Catalytic Decomposition of Biogas (CDB) to simultaneously produce syngas (SG) with high hydrogen contents and bio-carbon nanofibers (BCNFs) has been studied in detail [18,19]. As CNFs, BCNFs from biogas have initially a certain degree of structural order and therefore, they are classified within graphitic carbons.…”
Section: Introductionmentioning
confidence: 99%
“…The nickel domain size of the calcined fresh catalyst was 19 nm while after the reduction pre-treatment (under a H 2 flow at 550 °C) and passivation (under a 1% O 2 -99% N 2 flow at room temperature) was 31 nm. This catalyst has been extensively used and a thorough characterization can be found in previous works of our research group [19,24].…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…Operating conditions as temperature or feedstock composition (CH 4 :CO 2 ratio) are key factors [17,18]. Thermodynamic analysis revealed that high temperatures and/or CH 4 :CO 2 ratios below the unity are necessary to avoid carbon formation [19], even though from an industrial point of view the opposite conditions are more convenient.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the previous relative rates, catalyst deactivation could be prevented if steps ii) and iii) are faster than iv) [30]. Under these conditions, the front face of catalyst particles remain free of carbon, leaving accessible active sites to CH 4 and CO 2 and allowing the formation of NFC without catalyst deactivation [12,17,31]. With this background in mind, we recently addressed a novel approach to the decomposition of CH 4 /CO 2 mixtures (the so-called catalytic decomposition of biogas (CDB)) which consisted in the simultaneous production of syngas (H 2 and CO mixture) and bio-nanostructured filamentous carbon (BNFC) [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation